A rare doubly nitrato and phenoxido bridged trimetallic CuII complex: EPR, antiferromagnetic coupling and theoretical rationalization. Issue 60 (7th June 2016) - Datta, Amitabha; Das, Kuheli; Mane, Sandeep B.; Mendiratta, Shruti; El Fallah, Mohamed Salah; Garribba, Eugenio; Bauzá, Antonio; Frontera, Antonio; Hung, Chen-Hsiung; Sinha, Chittaranjan
Abstract : A new homometallic trinuclear Cu(ii ) complex is afforded with a tetradentate Schiff base precursor. Complex1 manifests a strong antiferromagnetic coupling which is in agreement with EPR and DFT computation to explain the magneto-structural correlation. Abstract : A rare trimetallic Cu II complex, [Cu3 (L)2 (NO3 )2 ] (1 ) has been afforded incorporating a [CuL] metalloligand, [where H2 L = N, N ′-bis(salicylidene)-1, 3-propanediamine]. In1, in addition to the double phenoxido bridge, the two terminal Cu II atoms are linked to the central Cu II by means of syn – anti bridging nitrate anions giving rise to a linear arrangement. Complex1 exhibits strong antiferromagnetic coupling and shows an χ M T value of 0.703 cm 3 mol −1 K at 300 K. DFT computational studies reveal that there is a clear magneto-structural correlation between the Cu–O–Cu angle and the J Cu–Cu values, which is in accordance with the experimental evidence. The biological effect of1 on the viability of different human carcinoma cells was evaluated using MTT assay and the results indicate that this complex induces a decrease in cell-population growth of human colorectal carcinoma cells (COLO 205) with apoptosis.